Comparative metabolomics of leaves and stems of three Italian olive cultivars under drought stress - Parri, Sara; Cai, Giampiero; Romi, Marco; Cantini, Claudio; Pinto, Diana C. G. A.; Silva, Artur M. S.; Dias, Maria Celeste Pereira (Frontiers in Plant Science, 2024)
The Mediterranean will be one of the focal points of climate change. The predicted dry and hot summers will lead to water scarcity in agriculture, which may limit crop production and growth. The olive tree serves as a model woody plant for studying drought stress and improving water resource management; thus, it is critical to identify genotypes that are more drought tolerant and perform better under low irrigation or even rainfed conditions. In this study, the metabolomic approach was used to highlight variations in metabolites in stems and leaves of three Italian olive cultivars (previously characterized physiologically) under two and four weeks of drought stress. Phenolic and lipophilic profiles were obtained by gas chromatography-mass spectrometry and ultra-high performance liquid chromatography-mass spectrometry, respectively. The findings identified the leaf as the primary organ in which phenolic variations occurred. The Maurino cultivar exhibited a strong stress response in the form of phenolic compound accumulation, most likely to counteract oxidative stress. The phenolic compound content of 'Giarraffa' and 'Leccino' plants remained relatively stable whether they were exposed to drought or not. Variations in the lipid profile occurred in leaves and stems of all the cultivars. A high accumulation of compounds related to epicuticular wax components was observed in the leaf of 'Giarraffa', while a strong reduction of lipids and long-chain alkanes occurred in 'Maurino' when exposed to drought stress conditions.